Familiares de pacientes alcoolistas: percepção e forma de lida - Costa Filho, Manoel Ramos (2003)
With the purpose of contributing to the understanding of some questions, which involve alcoholism, we aim at analyzing the way a family member perceives and deals with alcoholism of one of his fellow members. This study was conducted with six family members of alcoholic patients, assisted by the mental health care network (Day-Hospital and CAPS), in the city of São Luís (MA). To collect the data, we held the interview, following the outlined schedule, working this material through the Content Analyses (Bardin, 1997), applying the technical thematic analyses. The elaborated speeches present diacritic understanding on the subject and its insertion in the universe of chemical dependence. The symbolic exchange that occurs - family group with the "street group" - points at this distortion, since the disturbances in the relationship are filled with moral and behavioral references. As to establish the focus of the discussion on the question, the family group guides alt the complexity of its contribution to the problem to the dependent subject, for it is at him that all the frustrations and desreatizações of the family group as a whole are directly aimed, to which all the negative and emotional feelings are added. Exclusion creates conflicts so intense that the speeches on the chemical dependence make us think about the importance of hospitalization as a solution to the problem. It is not hard to understand that the family group directs complete attention to the family patrimony as a way to limit the extension of the problem. The seriousness of this fact expresses the dissonance between subjectivity and reality at the time of the collecting of significative elements to understand the problem. Obviously, not only the individual, but also the whole family group are involved in the process of social nonidentification, not only for the quality of the establishment of his interpersonal elations as a family group as well as his capacity to interact with the social phenomena. Finally, it is observed a deep contradiction in the speeches presented in the representation, which the surveyed group brings about to the question of chemical dependence, which, at first, must be strickly considered by the instances which deal with the question. Even if we create action strategies, intervention and/or interaction to the problem, we should consider the cultural and social circumstances. Although it is a rather intrinsic consequence, we visualize a pathologic context which is not absolutely understood and that, for its turn, needs to identify with more emphasis in which moment a chemical dependence is actually a pathologic entity: before, during or after use and/or overuse of chemical substances. Our study fits in the context of the search for answers to the questions of daily practice when dealing with specific clients as well as confronting different knowledge, which in a certain way, also searches for answers. The speeches, the representation and dramatization, therefore, an apprehension of subjectivity researched by us, shows some very significative factors: the constant necessity of the mental health and nursing psychiatrist in the search for other and new knowledge; rethinking the practice of caring and of who cares; creation of strategies of caring which really meets the proposed objectives as to the development of the therapeutic process; a more precise approach of the social surroundings of the disease, of the patient, and, especially, of the family group and its social context; methodologies of assistance which provide more resotutive as to dealing with the client; the apprehension of interdisciplinary as to the construction of a field in the production of knowledge. /